The Influence of Web Design Quality and Brand Image on Repurchase Intention with Customer Satisfaction as Mediating Variable - Hadioetomo Hadioetomo; Agus Sukarno; Hery Sutanto; Yuli Liestyana; Izah Nur Haniyah (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Technological and internet advancements have transformed entertainment consumption patterns, particularly through streaming platforms such as Netflix. Despite having a strong brand image, Netflix faces challenges in maintaining customer loyalty. This study aims to examine the influence of web design quality and brand image on customer satisfaction and repurchase intention, with customer satisfaction serving as a mediating variable. A quantitative approach was employed using an online survey. Data were collected from 104 Generation Z respondents in Yogyakarta who had active Netflix subscriptions, using purposive sampling. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results indicate that web design quality and brand image positively affect both customer satisfaction and repurchase intention. Moreover, customer satisfaction was found to mediate the relationship between web design quality and brand image on repurchase intention, strengthening their effects. These findings highlight the critical role of digital platform quality and brand reputation in fostering user loyalty. The study recommends that streaming service providers enhance platform functionality and usability while maintaining a strong brand image to improve customer satisfaction and retention.